The novel anti-colitic effect of β-adrenergic receptors via modulation of PS1/BACE-1/Aβ axis and NOTCH signaling in an ulcerative colitis model - Nasser, Salma; Abdallah, Dalaal M.; Ahmed, Kawkab A.; Abdel-Mottaleb, Yousra; El-Abhar, Hanan S. (Frontiers in Pharmacology, 2022)
Although dysautonomia was documented in inflammatory bowel disease, with activation of the stress-related sympathetic system, the role of agonists/antagonists of the adrenergic receptors is not conclusive. Moreover, ulcerative colitis was recently linked to dementia, but the potential role of the presenilin 1(PS1)/BACE-1/beta-amyloid (Aβ) axis has not been evaluated. Hence, we investigated the impact of mirabegron (β3-agonist) and/or carvedilol (β1/β2 antagonist) on iodoacetamide-induced ulcerative colitis with emphasis on the novel pathomechanism of the PS1/BACE-1/Aβ axis in ulcerative colitis, and its relation to the inflammatory cascade, fibrotic processes, and the gut barrier dysfunction. Ulcerated rats were either left untreated or treated for 8 days with mirabegron and/or carvedilol. Besides minimizing colon edema and weight loss, and improving colon structure, mirabegron and/or carvedilol abated colonic PS1/BACE-1/Aβ axis and the NOTCH1/NICD/HES1 hub besides the inflammatory cascade GSK3-β/NF-κΒ/TNF-α, and the oxidative stress marker malondialdehyde. The anti-fibrotic effect was verified by boosting SMAD-7 and inhibiting TGF-β1, α-SMA immunoexpression, and MTC staining. Moreover, the drugs improved the gut barrier function, attested by the increased goblet cells and expression of E-cadherin, and the inhibited expression of p(Y654)-β-catenin to preserve the E-cadherin/β-catenin adherens junction (AJ). These signaling pathways may be orchestrated by the replenished PPAR-γ, a transcription factor known for its anti-colitic effect. Conclusion: Besides maintaining the gut barrier, mirabegron and/or carvedilol mediated their anti-colitic effect by their anti-oxidant, anti-inflammatory, and anti-fibrotic capacities. The therapeutic effect of these drugs depends partly on suppressing the harmful signaling pathways PS1/BACE-1/Aβ, NOTCH1/NICD/HES1, GSK3-β/NF-κΒ/TNF-α, and TGF-1β/α-SMA while enhancing PPAR-γ, SMAD-7, mucus, and AJ.